Relación entre la divulgación de indicadores de rendimiento no financieros y el valor de mercado de las empresas que cotizan en bolsa - Romão, Bruno José Patrício (2023)
The development of this article aims to verify the relationship between the disclosure of non-financial performance indicators and the market value of publicly traded companies listed in the Brazilian Stock Exchange (B3). For this, the sustainability, annual, management and results release reports of 109 companies with shares listed on B3 were analyzed, in order to constitute the percentage of disclosure of non-financial indicators (DINF) of each organization that made up the research sample. To achieve the outlined objective, methodological content analysis procedures were carried out and later a median test (Kruskal-Wallis), a box-plot graph was also used to build the perception about the difference between the groups. The results show that, in general, companies with higher levels of disclosure of non-financial performance indicators tend to have a higher market value than those companies that practice more superficial disclosure.